Pengaruh Konflik Peran Ganda Dan Stress Kerja Terhadap Motivasi Kerja Pada Karyawan Perempuan (Studi Kasus PT.Manunggal Indowood Investindo) - Imro’atus Sholihah; Nur Hidayati; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to examine the effect of multiple role conflict, and job stress, on the work motivation of female employees at PT. Manunggal Indowood Investindo is located at Jl. Lumbang, Blk. Tempuran, Wringinom, Kec. Tongas, Probolinggo, East Java. The population used is female employees who are married. The sample used was 32 respondents. The analytical tool that the researcher uses is the spss analysis tool (Statistical Package for the Social Sciens).From this research, the following results are obtained: From this study it is concluded that both multiple role conflicts and work stresses both affect the work motivation of female employees who are married to PT Manunggal Indowood Investindo. The dual role conflict affects the work motivation of female employees who are married to PT Manunggal Indowood Investindo. Job stress affects the work motivation of female employees who are married to PT Manunggal Indowood Investindo. Keywords: Multiple Role Conflict, Job Stresss, Work Motivation